(untitled) (Cultura Económica, 2019)
The economist Juan Carlos de Pablo suggests in this article the updating of the long-running debate concerning the agricultural and industrial sectors in Argentina. From the now famous discussion on the “agro-exporter” model and looking in the current context that requires especial attention to the central role of China in the international economy, de Pablo wonders about the commercial and productive structure suitable for the country. Finally, the author reminds us of the importance of the cultural, social and political dimensions of the design of a national economic structure and strategy.